Strategy to Improve The Competitiveness of Cooperatives - Rusdarti, Rusdarti; Sakitri, Wijang (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
This research purposes is to analyze cooperative’s strategy to improve its competitiveness based on information technology utilization. This research employs a quantitative descriptive approach, analysis on cooperative competitiveness with Policy Analysis Matrix (PAM) in consideration of input and output. Cooperative’s business development strategy employs an analytic hierarchy process (AHP). The analysis is conducted on active cooperatives with open data system (ODS) in Central Java Province. 64.82% of all cooperatives have utilized information technology in their business operation and 35.18% of all cooperatives have not utilized information technology in their business operation; Result of the Policy Analysis Matrix (PAM) using the Domestic Resources Cost Ratio (DRC) = 0.240 This Condition shows that the cooperatives business is efficient and has comparative advatage. Private Cost Ratio (PCR) = 0.229, means the cooperative has been able to use its domestic use the actual price and has competitive advantage. Cooperative has comparative advantage and competitive advantage competitiveness. The results of AHP analysis with five development criteria show that the information technology criterion is the most prioritized criterion with weight value of 0.365; the capital criterion’s weight value is 0.218; the human resource criterion’s weight value is 0.195; the network criterion’s weight value is 0.164, and the marketing criterion’s weight value is 0.058. The cooperative competitiveness standard does not include export variable, thus further research needs to be conducted with different measuring tool from that of this research.